Chromosomal Characteristics of Human Preimplantation Embryos Assess by Comparative Genomic Hybridization (Global Journal of Medical Research, 2015)
Introduction-In recent years, more women are getting married and starting a family at an older age. Advanced maternal age (AMA) is defined as age 35 years or more for the mother. This group has been observed to have a high risk of chromosomal abnormalities in their embryos during pregnancy because the quality of oocytes correlate with maternal age and corresponding reproductive clinical outcomes (1). In 2013, Harton et al. reported that higher maternal age appears to be associated with increased risk of aneuploidy in embryos :42 yrs (92.6%) from 451 blastomeres and 42 yrs (84.8%) from 462 blastocysts (2). Moreover, Menken et al. reported on the effects of maternal age on fertility with a decrease in birth rates when maternal age is >/= 35 yrs (3). For this reason, assisted reproductive technology (ART) and preimplantation genetic screening (PGS) can be help to infertile couples and patients at high risk of there being chromosome abnormalities in the embryo. PGS is the technology used for screening chromosome abnormalities to selectively transfer euploid embryos in IVF. Patients using PGS have a higher implantation rate and pregnancy rate compared to those using morphological assessment of embryos alone (4-10).